Restriction Fragment Length Polymorphism (RFLP) gen sitokrom b dari delapan species burung - D.A. Wibowo .; W.E. Prasetyaningtyas .; I. Djuwita . (Hemera Zoa, 2010)
The aim of this research is to study the Restriction Fragment Length Polyorphism (RFLP) of eight species local birds of the cytochrome b mitochondrial DNA fiagment. The results gainedfiom this study is expected to be used as basic information for tissue birds species recognition. Eight bird I I tissues collected from Bogor area were preserved in 4,5 M NaCI containing 25% DMSO. DNA were isolated using ammonium acetat precipitation. Universal oligonucleotide cytochrome b primers L14841/H15149 were used for amplification of the mitochondrial cytochrome b DNA fragment using Polymerase Chain Reaction (PCR) method, followed by determination of the PCR product by electrophoresis. The amplicon were digested using restriction enzymes Hinf I (2,5 unit) and Rsa I (20 unit) for 2 and 6 hours, respectively. The calculation of the DNA amplicon and restriction fragment is done by measuring the distance between sample DNA migration with the DNA ladder in 2% agarose gel. The results showed that eight local birds species have 359 bp amplicon, and have different Hinf I restriction fragment size, except between scaly-breasted munia and streaked weaver, and also have difflerent Rsa I restriction fragment size except streaked weaver and javan turtle dove, and also chicken and yellow-vented bulbul. In conclusion, universal oligonucleotide cytochrome b primer followed by digestion with Hinf I and Rsa I restriction enzymes can be used for the eight birds species recognition.